Comparative study of two repetitive process control techniques for a grid-tie converter under distorted grid voltage conditions. (December 2019) - Jackiewicz, Krzysztof; Stras, Andrzej; Ufnalski, Bartlomiej; Grzesiak, Lech
Highlights: Frequency adaptive: multioscillatory control and repetitive control are studied. Methods are applied for a grid-tie converter. Memory and computational burden analysis of both methods are presented. A linear prewarping for frequency adaptive multioscillatory control is proposed. Practical implementation hints are provided. Abstract: The paper describes two main approaches of periodic control under variable frequency conditions: frequency adaptive multioscillatory control (FAMOSC) and fractional delay repetitive control (FDRC). The methods are applied in the control system of a grid-tie converter to increase the quality of phase currents in case of distorted grid voltages. The paper compares structures, performance and implementation of FAMOSC, FDRC and the conventional approach of repetitive and multioscillatory control. Performances of the control systems are illustrated with experiments on a laboratory test bench. The article describes tuning process of FDRC and FAMOSC with the usage of Particle Swarm Optimization algorithm. A detailed analyse and research of the techniques in terms of computational complexity is presented. Practical hints for implementation and resource optimization of both techniques on DSP are included. For FAMOSC a fast implementation of prewarping is proposed.